How important is it to consider target properties and hematocrit in bloodstain pattern analysis?. (September 2016) - Kim, Sungu; Ma, Yuan; Agrawal, Prashant; Attinger, Daniel
Highlights: Impact of blood drops on targets with varying material and roughness was investigated. A procedure is described to measure hematocrit during bloodstain pattern analysis experiments. Correlations relating the stain size and velocity of impact were developed. Uncertainty in hematocrit induces significant errors in BPA trajectory reconstruction. Consideration of target surface is needed for accurate BPA trajectory reconstruction. Abstract: Trajectory reconstruction from inspection of bloodstain patterns is relevant to crime scene investigation. While the influence of target properties on trajectory reconstruction has been often qualitatively discussed, it has rarely been quantified. Similarly, a few impact studies measure the viscosity of the blood used in impact experiments. In this work, the impact of blood drops is investigated on targets with a range of surface roughness and surface material. The maximum spreading is characterized using a spreading correlation, which relates the ratio of stain diameter to drop diameter with the non-dimensional numbers Reynolds number and Ohnesorge number. The process for obtaining individual spreading correlations for each of the target substrates and for measuring the viscosity of the respective blood samples is described extensively. The error in estimating the drop release height, associated with using an impact correlation unspecific to the target of interest, is estimated analytically and numerically using experimental data. A similar analysis is done when the hematocrit of the blood is assumed rather than measured. Both assumptions lead to significant errors in estimating the release height of a blood droplet.